USE OF MUSIC THERAPY IN NURSING CARE FOR PATIENTS - Reham Ibrahim Alharbi, Nada Abdullah Nolilley, Raydah Eid Jabber Almowalad, Munif Ayed Saleh Alrashidi, Ahlam Gharbi Alshammari, Khaled Mohammed Alsahli, Rahmah Muawwadh Almutairi, Abdulaziz Mohammed Mubarak Aldosari; Nourah ibrahim Almusaid, Amal mubarak Saeed Almutairi, Abdul Rahim Fayhan Bani Al-Rashidi, Eman Abdullah Suliman Almutary, Amani Abdallah Odah Alodah (Chelonian Research Foundation, 2022)
Integrative palliative and palliative treatment is a therapy approach that views patients as whole individuals made up of interconnected systems. The multidisciplinary treatment team is faced with the task of considering the ethical and efficient offer of comprehensive treatments that simultaneously address various systems at the end of life via cotreatment. Nurses and music medical professionals, as direct care professionals who often interact with patients as well as caregivers, are in a favorable position to work together in delivering comprehensive care. This article outlines the procedures that nurses and music therapists may use to handle family support, spirituality, mourning, and telemedicine. These processes include referral, evaluation, and treatment. Provided are clinical vignettes that demonstrate the development of cotreatment and its possible advantages in various situations. Within this framework, music therapy is established as an essential service in hospice care, rather than being considered an alternative or supplementary option. It fulfills the necessary counseling services outlined in Medicare's Rules of Participation for hospice practitioners. The deliberate and organized collaboration between nurses and musicians could offer patients and caregivers the opportunity to receive high-quality and complete care, which can facilitate smooth and healthy transitions throughout the dying process. Keywords: hospice, integrative medicine, palliative care, transdisciplinary, music therapy, nursing.